Willingness of community based health insurance uptake and associated factors among urban residents of Oromia regional state, Oromia, Ethiopia, a cross-sectional study - Alem Deksisa; Meyrema Abdo; Ebrahim Mohamed; Daniel Tolesa; Sileshi Garoma; Abate Zewdie; Melese Lami; Dinka Irena; Dereje Abdena; Hunde Lemi (BMC, 2020)
Abstract Background Globally, Millions of people cannot use health services because of the fear of payment for the service at the time of service delivery. From the agenda of transformation and the current situation of urbanization as well as to ensure universal health coverage implementing this program to the urban resident is mandatory. The aim of this study is to assess the willingness of community-based health insurance (CBHI) uptake and associated factors among urban residents of Oromia regional state, Oromia, Ethiopia, 2018. Methods A community-based cross-sectional study was conducted. From the total of eighteen towns; six towns which account for 33% of the total were selected randomly for the study. One population proportion formula was employed to get a total of 845 households. A pre-tested, semi-structured interviewer-administered questionnaire was used to collect the required data. Double-Bounded Dichotomous Choice Variant of the contingent valuation method was used to assess the maximum willingness to pay for the scheme, and a multiple logistic regression model was used to determine the effect of various factors on the willingness to join and willingness to pay for the households. Result About 839 (99.3%) of the respondents participated. The mean ages of the respondents were 40.44(SD ± 11.12) years. 621 (74.1%) ever heard about CBHI with 473 (56.3%) knowing the benefits package. Out of 839, 724 (86.3%) were willing to uptake CBHI of which 704 (83.9%) were willing to pay if CBHI established in their town. Conclusion If CBHI established about 86.3% of the households would enroll in the scheme. Having education, with a family size between 3 & 6, having difficulty in paying for health care and less than 20mins it took to reach the nearest health facility were the independent predictors of the willingness of CBHI uptake. The Oromia and Towns Health Bureau should consider the availability of health facilities near to the community and establishing CBHI in the urban towns.